Nitrogen Addition Altered the Effect of Belowground C Allocation on Soil Respiration in a Subtropical Forest - He, Tongxin (PLoS One, 2016)
The availabilities of carbon (C) and nitrogen (N) in soil play an important role in soil carbon dioxide (CO(2)) emission. However, the variation in the soil respiration (R(s)) and response of microbial community to the combined changes in belowground C and N inputs in forest ecosystems are not yet fully understood. Stem girdling and N addition were performed in this study to evaluate the effects of C supply and N availability on R(s) and soil microbial community in a subtropical forest. The trees were girdled on 1 July 2012. R(s) was monitored from July 2012 to November 2013, and soil microbial community composition was also examined by phospholipid fatty acids (PLFAs) 1 year after girdling. Results showed that R(s) decreased by 40.5% with girdling alone, but N addition only did not change R(s). Interestingly, R(s) decreased by 62.7% under the girdling with N addition treatment. The reducing effect of girdling and N addition on R(s) differed between dormant and growing seasons. Girdling alone reduced R(s) by 33.9% in the dormant season and 54.8% in the growing season compared with the control. By contrast, girdling with N addition decreased R(s) by 59.5% in the dormant season and 65.4% in the growing season. Girdling and N addition significantly decreased the total and bacterial PLFAs. Moreover, the effect of N addition was greater than girdling. Both girdling and N addition treatments separated the microbial groups on the basis of the first principal component through principal component analysis compared with control. This indicated that girdling and N addition changed the soil microbial community composition. However, the effect of girdling with N addition treatment separated the microbial groups on the basis of the second principal component compared to N addition treatment, which suggested N addition altered the effect of girdling on soil microbial community composition. These results suggest that the increase in soil N availability by N deposition alters the effect of belowground C allocation on the decomposition of soil organic matter by altering the composition of the soil microbial community.